BlockChain platforms in financial services: Current perspective - Pablo Garcia Bringas; Iker Pastor-López; Giuseppe Psaila (Business Systems Research (BSR), 2020)
Background BlockChain technology was invented to support bitcoin, currently the most popular virtual currency. Objectives The purpose of this paper is to investigate contemporary BlockChain platforms in financial services. Methods/Approach An unstructured literature review has been used. Results BlockChain in financial services is mostly associated with bitcoin exchange. However, this is a partial view of both BlockChain technology and its possible adoption for financial services: in fact, many BlockChain platforms are now available and many different financial services can be effectively supported by BlockChain platforms, even though they are not based on virtual-money exchange. Furthermore, people are attracted by the concept of smart contract, i.e., a contract that is automatically executed by computer technology, without human intervention. Conclusions The contribution of this paper is twofold: first of all, we introduce the four BlockChain platforms that are now most popular, discussing how they support the smart contract concept; second, we identify some typical categories of financial services, matching each of them with the platform that provides the best support for each category.
Keywords: L86; 330; BlockChain history; BlockChain characterization; smart contracts; perspective BlockChain in financial services